MamF-like proteins are distant Tic20 homologs involved in organelle assembly in bacteria - Anja Paulus; Frederik Ahrens; Annika Schraut; Hannah Hofmann; Tim Schiller; Thomas Sura; Dörte Becher; René Uebe (Nature Communications)
Abstract Organelle-specific protein translocation systems are essential for organelle biogenesis and maintenance in eukaryotes but thought to be absent from prokaryotic organelles. Here, we demonstrate that MamF-like proteins are crucial for the formation and functionality of bacterial magnetosome organelles. Deletion of mamF-like genes in the Alphaproteobacterium Magnetospirillum gryphiswaldense results in severe defects in organelle positioning, biomineralization, and magnetic navigation. These phenotypic defects result from the disrupted targeting of a subset of magnetosomal proteins that contain C-terminal glycine-rich integral membrane domains. Phylogenetic analyses reveal an ancient evolutionary link between MamF-like proteins and plastidial Tic20. Our findings redefine the molecular roles of MamF-like proteins and suggest that organelle-specific protein targeting systems also play a role in bacterial organelle formation.